Effects of specific training programs on punch performance - Pinto, M.; Crisóstomo, J.; Kirk, C.; Abián-Vicén, J.; Monteiro, L. (Sports, 2026)
Punch impact power is crucial for boxing performance and varies with punch biomechanics. Straight punches rely primarily on linear force production, whereas Hook punches depend more on rotational and lateral force generation; however, the effectiveness of strength and conditioning (S&C) interventions remains insufficiently explored. This study investigated the effects of targeted S&C programs on Straight and Hook punch impact power in trained boxers compared with regular boxing training. Thirty-one boxers completed an eight-week intervention and were allocated to three groups: a Linear-Oriented Training Group (LOTG), a Rotational-Oriented Training Group (ROTG), or a Control Group (CG). Punch impact power (Jab, Cross, Lead Hook, and Rear Hook) was assessed using PowerKube at baseline and post-intervention. One-repetition maximum bench press (1 RM BP), countermovement jump (CMJ), and handgrip strength (HS) were also evaluated. Data were analyzed using mixed-design repeated-measures ANOVA and one-way ANOVA on post-pre change scores. A significant main effect of time was observed for all punch types (p < 0.001), with significant group × time interactions for the Cross, Lead Hook, and Rear Hook (p < 0.05). The ROTG showed the greatest improvements, particularly in Hook punches. Targeted S&C interventions, particularly rotational training, improved punching impact power and neuromuscular performance.